Complementary music education and its impacts on secondary music curriculum - Hamilton, Natalie (Kansas State University, 2022)
Music education in schools has become disassociated with students’ out of school musical experiences. The teaching model used in secondary schools is, “…that of the autocratic, professional conductor of a large, classical ensemble” (Kratus, 2007, p.45). A central question to ask of music educators, “Is that the model of music making we want for our students?” (ibid.). In 2016, 3.5 million students graduated from high school in the United States. Of the 3.5 million, 1 million students would go on to graduate with a bachelor’s degree in 2020 and 3,264 students (.0032%) graduated with a Bachelor of Music Education ( U.S. Department of Education, 2020; Digest of Education Statistics, 2017; Data USA, 2021). If we want to be more inclusive in secondary music education, then one part of the process is to discover what teachers are already doing to diversify their curriculum. This study identifies current beliefs and practices of secondary music educators on curricular diversification at the secondary level. When asked in a survey if they offer courses beyond traditional band, orchestra, and choir (BOC), 57.23% of 380 secondary music educators in the state of Kansas responded "yes,” while 42.68% answered “no.” Teachers who selected “yes” gave examples of courses they teach such as guitar, piano, class voice, music theory, musical theatre, music in media and many more. For the many teachers who answered “no,” adding another class such as piano, guitar or music in media can be outside of the realm of current possibility. Therefore, many remain in the cycle of traditional music education. Based on this data, one way to be more inclusive is to adjust the ensemble curriculum from within to broaden possibilities for teachers in manageable ways, building on their strengths, capabilities, and communities. The term I use to describe these possibilities is “Complementary Music Education.”
Keywords: Music education; Complementary music education; Secondary ensemble curriculum; Expanding secondary music; Diversifying secondary ensemble curriculum